Gorlin-Goltz Syndrome: Case Report of a Rare Hereditary Disorder. (23rd September 2012) - Agrawal, Ashutosh; Murari, Aditi; Vutukuri, Sunil; Singh, Arun
Abstract : Introduction . Gorlin-Goltz syndrome is an inherited autosomal dominant disorder with complete penetrance and extreme variable expressivity. Case Report . The present paper highlights the importance of diagnostic criteria and histopathology in early and prompt diagnosis which will lead to proper treatment and genetic counseling of the patient. Discussion . Gorlin-Goltz syndrome is about multisystem process comprising the triad of basal cell nevi, jaw keratocysts, and skeletal anomalies. A spectrum of other neurological, ophthalmic, endocrine and genital manifestations is known to be variably associated with this triad. Diagnosis of the syndrome is based on major and minor criteria. Conclusion . This paper emphasizes the importance of oral and maxillofacial health professionals in the early diagnosis of nevoid basal cell carcinoma syndrome and in a preventive multidisciplinary approach to provide a better prognosis to the patient.